2009
DOI: 10.1177/0145482x0910300705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Visual Impairments in Adults with Cognitive and Developmental Disabilities in a Sheltered Workshop in Germany

Abstract: Individuals with cognitive and developmental disabilities have a high probability of visual impairment. This study revealed the effects of deficits in the appropriate diagnosis of vision and medical treatment, as well as the lack of necessary refraction correction and support, specifically for adults with intellectual and developmental disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…found that timely detection and treatment of visual impairment amongst people with learning disabilities can positively influence their daily functioning. In Germany, Henriksen & Degenhardts (2009) conducted the first study in their country of 241 adults with learning disabilities and found a great number (54%) had visual acuity and visual impairment. What was interesting about Henriksen & Degenhardt’s study is that staff caring for people with learning disabilities was unaware of these impairments before the study.…”
Section: Introductionmentioning
confidence: 99%
“…found that timely detection and treatment of visual impairment amongst people with learning disabilities can positively influence their daily functioning. In Germany, Henriksen & Degenhardts (2009) conducted the first study in their country of 241 adults with learning disabilities and found a great number (54%) had visual acuity and visual impairment. What was interesting about Henriksen & Degenhardt’s study is that staff caring for people with learning disabilities was unaware of these impairments before the study.…”
Section: Introductionmentioning
confidence: 99%
“…Im Vergleich zu den bei Angehörigen lebenden Teilnehmern nehmen die aus Wohnheimen öfter am Check-up, an der Hautkrebsvorsorge, der Gebärmutterhals-und Tastuntersuchung der Brust teil, doch seltener an der Gesundheitsförderung. [15,7] vor 1-2 Jahren 16 [15] 9,4 [8,7] vor 2-5 Jahren 11 [5] 6,5 [2,9] vor mehr als 5 Jahren 9 [30] 5,3 [17,4] weiß ich nicht 5 [ Mit 97 % geben fast alle einen festen Hausarzt an, den sie zuerst bei Gesundheitsproblemen aufsuchen. Darüber hinaus werden insbesondere Nerven-, HNO-, Haut-, Augenärzte und Orthopäden deutlich häufiger in Anspruch genommen.…”
Section: Discussionunclassified
“…Der Teilhabebericht der Bundesregierung beschränkt sich auf Personen, die in Privathaushalten leben und einen vorstrukturierten Fragebogen beantworten können [13]. Die vorhandenen internationalen und deutschen Studien geben jedoch Hinweise auf ungedeckte Gesundheitsbedarfe bei Gehör [14], Augen [15], Haut [16], Zähnen [17,18], Bewegungsapparat [19] und beim Impf-schutz [20,21] sowie undiagnostizierte Krankheiten des metabolischen Syndroms [22] und niedrige Inanspruchnahme von Vorsorgeuntersuchungen [23,24]. Studien weisen auch auf erhöhte Gesundheitsrisiken durch Lebensstilfaktoren hin, v. a. hinsichtlich körperlicher Bewegung und Körpergewicht, und damit auf Bedarf nach Verhaltensprävention [23,25,26].…”
Section: Introductionunclassified